1969
DOI: 10.1901/jeab.1969.12-917
|View full text |Cite
|
Sign up to set email alerts
|

AVERSIVE PROPERTIES OF THE NEGATIVE STIMULUS IN A SUCCESSIVE DISCRIMINATION1

Abstract: Experiment I sought to determine if the stimulus correlated with extinction in a successive discrimination was an aversive stimulus. An escape response provided an index of aversive control. Two groups of pigeons were exposed to a multiple variable-interval 30-sec extinction schedule. For the experimental group, a single peck on a second key produced a timeout during which all lights in the chamber were dark. For the control group, pecks on the second key had no contingency. The rate of responding on the timeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
1
2

Year Published

1972
1972
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 15 publications
4
41
1
2
Order By: Relevance
“…For example, pigeons and/or rats have been reported to obtain time-outs from various simple fixed-ratio (Appel, 1963;Azrin, 1961;Dardano, 1973;Thompson, 1964Thompson, , 1965 and fixed-interval (Brown & Flory, 1972) schedules, as well as from various component schedules of a multiple schedule of food reinforcement (Rilling, Askew, Ahlskog, & Kramer, 1969;Terrace, 1968; a multiple schedule requires the successive presentation of two or more independent schedules of reinforcement, each in the presence of a different exteroceptive stimulus). Since many investigators (e.g., Azrin, 1961;Rilling, et aI., 1969;Terrace, 1968) consider the time-out response to be an escape response and, thus, a quantitative index of aversiveness, it is surprising that relatively few studies have examined conditions under which time-outs are obtained from a stimulus associated with both positive reinforcement and the known aversive stimulus, electric shock (Azrin & Holz, 1966).…”
Section: Colorado State University Fort Collins Colorado 80521mentioning
confidence: 99%
“…For example, pigeons and/or rats have been reported to obtain time-outs from various simple fixed-ratio (Appel, 1963;Azrin, 1961;Dardano, 1973;Thompson, 1964Thompson, , 1965 and fixed-interval (Brown & Flory, 1972) schedules, as well as from various component schedules of a multiple schedule of food reinforcement (Rilling, Askew, Ahlskog, & Kramer, 1969;Terrace, 1968; a multiple schedule requires the successive presentation of two or more independent schedules of reinforcement, each in the presence of a different exteroceptive stimulus). Since many investigators (e.g., Azrin, 1961;Rilling, et aI., 1969;Terrace, 1968) consider the time-out response to be an escape response and, thus, a quantitative index of aversiveness, it is surprising that relatively few studies have examined conditions under which time-outs are obtained from a stimulus associated with both positive reinforcement and the known aversive stimulus, electric shock (Azrin & Holz, 1966).…”
Section: Colorado State University Fort Collins Colorado 80521mentioning
confidence: 99%
“…Coughlin (1972) has questioned whether it is the aversiveness of S-that supports time-out responding. Coughlin (1970;cited in Coughlin, 1972cited in Coughlin, , 1973 was unable to replicate the findings of Rilling et al (1969) when the effects of stimulus change were controlled. Coughlin (1972) found that the addition of electric shock punishment for operant-key responding during S-, a procedure one would expect to increase the aversiveness of S-, actually decreased the rate of responding on the time-out key.…”
mentioning
confidence: 94%
“…Time-out responding from S+ was virtually nonexistent. Although they eliminated several alternatives to the escape from S-account of their data, Rilling et al (1969) pointed out that positive reinforcement by stimulus change rather than negative reinforcement by termination of S-could not be ruled out. Terrace (1971) included conditions to control for displaced pecking and stimulus change.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Since the empirical reality of these phenomena has been demonstrated (Reynolds, 1961;Rilling, Askew, Ahlskog, & Kramer, 1969; Terrace, 1971), it would seem to be incumbent upon proponents of gradient-interaction theory to show how the theory might be expanded to account for the foregoing byproducts.…”
mentioning
confidence: 99%